Experimental assessment of the gray cast iron production by inoculant injection - Reyes-Castellanos G.; Cruz-Ramírez A.; Gutiérrez-Pérez Hugo V.; Rivera-Salinas J.E.; Sánchez-Alvarado R.G.; Colin-García E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
An initial assessment of the gray cast irons production by injecting an inoculant with a conveying gas into a molten iron bath was evaluated at a laboratory scale. A numerical simulation was carried out to determine the hydrodynamic behavior between the inoculant particles injected into the molten iron. It was determined that an optimal interaction between the particles with the molten iron occurred at a lance depth of 7 cm and for the particle sizes fine (211 to 297 μm) and medium (421 to 590 μm), and the residence time was of 0.38 and 0.4 s, respectively. The melting time was calculated at 0.0008 and 0.003 s for the particle sizes fine and medium, respectively. After the injection, the FeSi of the inoculant melted quickly, releasing the elements of the inoculant which interacted with the molten iron and formed oxides and sulfides creating nucleating sites during solidification. The injection technique allowed obtaining a type-A graphite distribution for the fine and medium particle sizes. The number of eutectic cells increased when the inoculant particle size decreased despite of the low graphitisers elements and manganese contents used in the gray cast iron manufacturing.